Therapeutic Communication with Patient Anxiety Levels During Operation Preparation: A Cross-Sectional Study - Mahyuvi, Tata; Masqurotin, Masqurotin; Rumpiati, Rumpiati (Alta Dharma Publisher, 2023)
Background: Good therapeutic communication, besides being able to create a therapeutic relationship between nurses and patients, can also have an impact on improving the patient's psychology, including eliminating anxiety. Objective: This study aimed to determine the relationship between therapeutic communication and the patient's stress level when preparing for surgery in the Inpatient Room of the Surabaya A.Yani Islamic Hospital. Methods: Analytical research design with a correlational analytic approach. The sample size is 64 respondents with a purposive sampling technique. The independent variable is therapeutic communication, and the dependent is anxiety. The data collected using questionnaires on nurses' therapeutic communication and patient anxiety was given directly to patients. Analysis using Chi-Square. Results: The study's results of 64 respondents were obtained; most (60.9%) stated that the nurse's therapeutic communication was good, and most (60.9%) indicated they did not experience anxiety when undergoing surgery. There is a relationship between therapeutic communication and the patient's stress level during surgery preparation at the Surabaya A.Yani Islamic Hospital. Conclusion: Nurses in the ward with good therapeutic communication will reduce patient anxiety during surgery preparation. Recommendation: Nurses are expected to consistently provide good therapeutic communication to create a calm and comfortable atmosphere for patients in the hospital. It is necessary to research further the factors that can influence therapeutic communication and aspects of patient anxiety